2021
DOI: 10.1183/23120541.00715-2020
|View full text |Cite
|
Sign up to set email alerts
|

Long-term adherence to inhaled corticosteroids and asthma control in adult-onset asthma

Abstract: BackgroundIn short-term studies, poor adherence to inhaled corticosteroids (ICS) has been associated with worse asthma control, but the association of long-term adherence and disease control remains unclear.ObjectiveTo assess the relationship between 12-year adherence to ICS and asthma control in patients with adult-onset asthma.MethodsAs part of the Seinäjoki Adult Asthma Study, 181 patients with clinically confirmed new-onset adult asthma and regular ICS medication were followed-up for 12 years. Adherence (%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
(92 reference statements)
1
9
1
Order By: Relevance
“…[38][39][40] Poor adherence to ICS may lead to enhanced lung function decline, especially when asthma is not controlled (ie, symptomatic needing SABA). 25,41 However, we did not find any difference in lung function measurements or lung function decline between the patients with high or low SABA use over the 12 years. Moreover, an Australian study reported that SABA overusers were more likely to have depression (11.1% vs 5.7%), and a higher proportion of SABA overusers had uncontrolled asthma.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…[38][39][40] Poor adherence to ICS may lead to enhanced lung function decline, especially when asthma is not controlled (ie, symptomatic needing SABA). 25,41 However, we did not find any difference in lung function measurements or lung function decline between the patients with high or low SABA use over the 12 years. Moreover, an Australian study reported that SABA overusers were more likely to have depression (11.1% vs 5.7%), and a higher proportion of SABA overusers had uncontrolled asthma.…”
Section: Discussioncontrasting
confidence: 60%
“…The 12-year adherence was calculated by comparing cumulative dispensed doses of ICS (mg) with cumulative prescribed doses of ICS (mg) by using a method combining medication possession ratio and proportion of days covered formulas (Figures E2 and E3, available in this article's Online Repository at www.jaci-inpractice.org) (see this article's Online Repository at www.jaci-inpractice.org). 19,25 High SABA use was defined as !36 SABA canisters in 12 years, corresponding to an average of !3 dispensed canisters per year. 1,5,7,10 SABA over-reliance was classified into 3 categories: (1) high SABA use (!36 canisters in 12 years) and no dispensed ICS canisters during the follow-up; (2) high SABA use and <36 dispensed canisters of ICS (corresponding to <3 dispensed canisters per year on average); and (3) high SABA use and fewer ICS than SABA canisters dispensed.…”
Section: Assessment Of Dispensed Saba and Icsmentioning
confidence: 99%
“…Additionally, Cluley et al and Bosley et al [ 27 , 28 ] measure adherence over 8–10 weeks, while the present study uses long-term adherence over 12 months based on pharmacy redemption data. Indeed, a recent study finds that short-term and long-term adherence often differ substantially, emphasizing that the period of time over which one measures adherence is key [ 29 ]. In accordance with our study, Toelle et al [ 15 ] found no association between ICS adherence and MMD symptoms; in fact, depression symptoms was even associated with a lower risk of non-adherence.…”
Section: Discussionmentioning
confidence: 99%
“…For example, noncontrolled asthma combined with less than 80% adherence to ICS has been associated with faster lung function decline versus noncontrolled asthma with 80% or greater adherence. 9 Of the patients in the obese cluster, 96% were not currently working, 60% were receiving a disability pension, 28% had depression, and the average income was the lowest of any cluster. Socioeconomic status was the lowest in the obese and smoking clusters, and financial issues were often associated with poor adherence in the obese versus other clusters, even in Finland, which has a special asthma medication reimbursement system and relatively low medication expenses for patients.…”
mentioning
confidence: 97%